Analisis Resepsi Mahasiswa Muslim Terhadap Pemberitaan Tribun News.com Tentang Pemboikotan McDonald's - Safitri, Susi (Jurnal Spektrum Komunikasi, 2024)
A topic that has garnered national attention from 2023 forward is McDonald's contribution of 4,000 meals to the Israeli army. Since the topic was deemed contentious, it was also covered by a number of news outlets. Tribun News.com was among the media outlets that reported the story as well. When it comes to covering McDonald's acts and their effects on society, Tribun News.com is a very informed source. The goal of this research is to learn more about how Muslim students' opinions and behavior are influenced by the media, particularly the news media. Understanding the existing background of cultural and religious variety, as well as how the media influences the dynamics of diversity among Muslim students, is another goal of this research. This research contributes to the understanding of how Muslim students receive and interpret information from the media. These findings can also be used to improve the media's understanding of how to convey information more effectively to Muslim audiences. This study takes a descriptive approach while utilizing a qualitative strategy. Interviews with informants about how Muslim students reacted to news from Tribun news.com yielded data. In-depth interviews with carefully chosen informants and content analysis of Tribun News.com articles regarding the McDonald's boycott were used to gather data. The collected qualitative data were subjected to many analyses in this study: data collecting, data reduction through the summarization and selection of key elements from the interview transcripts, and data presentation by the combination of multiple transcripts from the same interview. The majority of informants are then in a dominant position following the data summary. According to this stance, Muslim students support the boycott as a way to protest McDonald's Israel's acts, and informants are important for comprehending the news that Tribun News.com provides.